Rutinitas Penerapan Baca Yasin Bersama Untuk Membentuk Karakter Siswa di MIS Hidayatul Muhajirin Kota Palangka Raya - Sardina Lorenza; Setria Utama Rizal (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The formation of religious character is a habit that is carried out to shape the student's personality so that they have morals and character that are embedded in the student as a guide for life in the future. To make this happen, schools are trying to find new programs that can grow student character and improve the quality of education at school. One of the efforts made by MIS Hidayatul Muhajirin to shape the religious character of these students is by implementing regular Yasin reading activities together. This research uses a descriptive qualitative approach with literature study methods and field practice which is directly followed by researchers at MIS Hidayatul Muhajirin Palangka Raya City starting from July to November 2024. The data collection techniques used in this research are observation, interviews and documentation. The results of this research show that the activity of implementing Yasin reading together regularly, which is carried out every Saturday morning at MIS Hidayatul Muhajirin, Palangka Raya City, which is attended by all students, teachers and students of MBKM IAIN Palangka Raya, is able to shape the students' religious character through refraction which is carried out every morning through activities and positive things from the routine of implementing Yasin reading together to create a generation that has good morals and behavior in line with the teachings of the Islamic religion.